Nopol synthesis over Sn-MCM-41 and Sn-kenyaite catalysts (2005)
ABSTRACT: Several methods were used to prepare Sn loaded kenyaite and MCM-41 silicates: ion exchange, incipient wetness impregnation and chemical vapor deposition. Catalysts were evaluated for nopol synthesis by the Prins condensation of b-pinene and paraformaldehyde. The resulting catalysts were characterized by elemental analysis, TGA, XRD, FTIR, BET surface area and UV–vis. Kenyaite samples modified with Sn by ion exchange were more resistant to leaching than those modified by chemical vapor deposition (CVD), while Sn-MCM-41 samples prepared by CVD were more active, selective to nopol and resistant to leaching than Sn-MCM-41 prepared by impregnation. In general, Sn-MCM-41 catalysts even at low Sn loadings exhibited higher nopol yields than Sn-kenyaite. Keywords: Nopol; b-Pinene; Prins reaction; Kenyaite; MCM-41; CVD; Ion exchange; Sn